2020
DOI: 10.1093/tropej/fmaa066
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Infants with Congenital Zika Virus Infection in Ecuador: A Retrospective Longitudinal Study

Abstract: Background Few congenital Zika syndrome (CZS) cases have been notified in Ecuador and, to our knowledge, there are no significant published studies dealing with their clinical evolution. We present a detailed clinical characterization of 21 children with congenital Zika virus (ZIKV) infection born in Ecuador who were followed up until September 2019. Methods We did a retrospective longitudinal study of children attended by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Similar studies from different regions of Brazil found high rates of severe motor impairments, epilepsy, and impairments in vision, hearing, and swallowing during childhood follow-up [69][70][71]. In a study from Ecuador of 16 infants with CZS, all had neurodevelopmental delays, spasticity, and hyperreflexia, 14 had seizures, 6 had SNHL, and 2 died prior to 24 months [72].…”
Section: Toxoplasmosismentioning
confidence: 61%
“…Similar studies from different regions of Brazil found high rates of severe motor impairments, epilepsy, and impairments in vision, hearing, and swallowing during childhood follow-up [69][70][71]. In a study from Ecuador of 16 infants with CZS, all had neurodevelopmental delays, spasticity, and hyperreflexia, 14 had seizures, 6 had SNHL, and 2 died prior to 24 months [72].…”
Section: Toxoplasmosismentioning
confidence: 61%
“…The head circumference at birth for children with microcephaly has also been associated with severe neurodevelopmental delay, severe neuroimaging findings, dysphagia, spasticity, hyperreflexia, hearing loss and epilepsy, according to the Garcia-Boyano et al (2020) cohort study [ 33 ]. A cohort study of Quilião et al published in 2020 [ 34 ] describes the findings of a cohort of children with CZS in terms of their head circumference and neurological-neurodevelopmental outcomes.…”
Section: Resultsmentioning
confidence: 99%